2006
DOI: 10.1256/qj.05.77
|View full text |Cite
|
Sign up to set email alerts
|

Observability of the Irminger Sea circulation using variational data assimilation

Abstract: SUMMARYThis paper explores the prospects for constraining circulation and stratification estimates in the Irminger Sea and Denmark Strait using variational data assimilation. A regional circulation model with 9 km horizontal grid spacing, seven vertical levels and open boundaries is used. The circulation it simulates is realistic in several important respects and includes a chaotic mesoscale eddy field. Pulsation of the outflow of dense water through the Denmark Strait is also reasonably realistic, although en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…Third, the MITgcm has useful features that will be exploited in the future: namely, its nonhydrostatic capability and the packages to simulate snow and sea ice dynamics (Zhang et al 1999;Zhang and Rothrock 2000). Finally, previous configurations have been already set up in the same area (Lea et al 2006;Haine et al 2009;Haine 2010).…”
Section: A Numerical Setupmentioning
confidence: 99%
“…Third, the MITgcm has useful features that will be exploited in the future: namely, its nonhydrostatic capability and the packages to simulate snow and sea ice dynamics (Zhang et al 1999;Zhang and Rothrock 2000). Finally, previous configurations have been already set up in the same area (Lea et al 2006;Haine et al 2009;Haine 2010).…”
Section: A Numerical Setupmentioning
confidence: 99%
“…Applying 4D‐Var to a regional, high‐resolution ocean circulation model with realistic physics is a good strategy to capture aspects of the real flow in energetic regions. There have been only a few studies in this direction [ Gebbie , 2004; Gebbie et al , 2006; Lea et al , 2006; Losch et al , 2008; Mazloff , 2008], however, mainly because of the technical challenge, and further experience is needed. Performing high‐resolution regional data assimilation in the SO using 4D‐Var is the subject of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In regimes in which modeled flows are expected to be balanced, it has been found that 4D data assimilation can cause the excitation of spurious unbalanced motion, essentially because of the development of unphysical correlations (Polavarapu et al 2000;Lea et al 2002;Houtekamer and Mitchell 2005;Neef et al 2006, hereafter NPS06) A general solution to this problem involves imposing balance constraints on the analysis (Courtier and Talagrand 1990;Dee 1991;Todling and Cohn 1994;Polavarapu et al 2000;Kepert 2004) or simply filtering out fast waves. In the upper stratosphere and mesosphere, excessive filtering can eliminate important gravity waves and either remove or amplify the tides (Sankey et al 2007).…”
Section: Introductionmentioning
confidence: 99%